Exploring Disparities in Gill Physiological Responses to NaHCO3-Induced Habitat Stress in Triploid and Diploid Crucian Carp (Carassius auratus): A Comprehensive Investigation Through Multi-Omics and Biochemical Analyses - Shicheng Han; Lin Han; Fangying Yuan; Wenzhi Liu; Jing Wang; Xiaofeng Jin; Yanchun Sun (Metabolites)
Background: Owing to the progressive rise in saline waters globally, resulting in detrimental impacts on freshwater aquaculture, the underlying molecular distinctions governing the response to alkaline stress between diploid and triploid crucian carp remain unknown. Methods: This investigation explores the effects of 20 and 60 mmol NaHCO3 stress over 30 days on the gills of diploid and triploid crucian carp, employing histological, biochemical, and multi-omic analyses. Results: Findings reveal structural damage to gill lamellas in the examined tissue. Diploid crucian carp exhibit heightened activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and alkaline phosphatase (AKP), alongside lower malondialdehyde (MDA) and urea nitrogen (BUN) levels compared to triploid counterparts. Metabolomic investigations suggest alterations in purine metabolism, lipid metabolism, sphingolipid metabolism, and aminoglycan and nucleotide sugar metabolism following NaHCO3 exposure. Transcriptomic data indicate differential expression of genes associated with nitrogen metabolism, complement and coagulation cascades, IL-17 signaling pathways, and Toll-like receptor signaling pathways. Conclusions: Overall, NaHCO3-induced stress leads to significant gill tissue damage, accompanied by reactive oxygen species (ROS) production causing oxidative stress and disruptions in lipid metabolism in crucian carp. Furthermore, an inflammatory response in gill cells triggers an immune response. Diploid crucian carp exhibit superior antioxidant and immune capacities compared to triploid counterparts, while also displaying reduced inflammatory responses in vivo. Notably, diploid carp efficiently excrete excess BUN through purine metabolism, mitigating protein metabolism and amino acid imbalances caused by BUN accumulation. This enables them to allocate less energy for coping with external environmental stress, redirecting surplus energy toward growth and development. The above results indicate that diploid organisms can better adapt to saline–alkaline environments. Overall, this study provides novel perspectives into species selection of crucian carp of different ploidy in saline–alkaline waters.